Modelling the response of freshwaters to catchment-scale phosphorus loading and mitigation in the Irish Ecoregion - Greene, Sheila (Trinity College (Dublin, Ireland). Department of Geography, 2012)
Freshwater eutrophication, caused by over-enrichment by P as a result of anthropogenic activity, is increasing worldwide. In response, ROMs that seek to reduce and reverse eutrophication and its effects through the mitigation of inputs of P have been implemented at national and international levels. Current European legislation requires effective mitigation of P loss from catchments containing freshwaters classified as below good status or at risk of not reaching good status by 2015 to be fully implemented by the end of 2012. However, meeting good status poses a major challenge for the Irish Ecoregion. Although measures targeted at preventing P loss from catchments have been implemented, there is inadequate information available on the most appropriate ROMs in different environmental settings.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin.